2017
DOI: 10.1002/2211-5463.12324
|View full text |Cite
|
Sign up to set email alerts
|

Covalent bonding of heme to protein prevents heme capture by nontypeable Haemophilus influenzae

Abstract: Nontypeable Haemophilus influenzae (NTHi) are Gram‐negative pathogens that contribute to a variety of diseases, including acute otitis media and chronic obstructive pulmonary disease. As NTHi have an absolute requirement for heme during aerobic growth, these bacteria have to scavenge heme from their human hosts. These heme sources can range from free heme to heme bound to proteins, such as hemoglobin. To test the impact of heme structural factors on heme acquisition by NTHi, we prepared a series of heme source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…NTHi is particularly susceptible to heme restriction as it lacks the necessary enzymes for its synthesis and relies solely on scavenging heme from the host, either in the form of free heme or bound to host carrier molecules [16,[21][22][23]. Evidence from our laboratory suggests that closely related commensals may present a competitive challenge for heme acquisition in the URT.…”
Section: Introductionmentioning
confidence: 96%
“…NTHi is particularly susceptible to heme restriction as it lacks the necessary enzymes for its synthesis and relies solely on scavenging heme from the host, either in the form of free heme or bound to host carrier molecules [16,[21][22][23]. Evidence from our laboratory suggests that closely related commensals may present a competitive challenge for heme acquisition in the URT.…”
Section: Introductionmentioning
confidence: 96%
“…Heme is not only essential for life but also an expensive molecule to synthesize. Organisms go to great lengths to regulate its production but also to reuse it when possible and acquire it from their environment, as seen, for example, with bacterial pathogens and their heme acquisition systems . Here, we conclusively show that organisms like the nematode C. elegans , have developed specialized systems to extract heme even when it is covalently bound, like in cytochromes c .…”
Section: Discussionmentioning
confidence: 70%
“…Organisms go to great lengths to regulate its production but also to reuse it when possible and acquire it from their environment, as seen, for example, with bacterial pathogens and their heme acquisition systems [8,36,37]. Here, we conclusively show that organisms like the nematode C. elegans, have developed specialized systems to extract heme even when it is covalently bound, like in cytochromes c. This observation, which contrasts with the recently reported failure of H. influenzae to capture heme from c-type cytochromes [8], has the potential to lead to the discovery of an entirely new class of hemehandling proteins which are not necessarily limited to heme auxotrophs. In the case of parasitic protists, like T. brucei, which also acquire their heme externally, such a discovery could be particularly significant as it might identify a new target for the development of compounds which could limit the growth of these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to soluble heme, NTHI are able to extract heme from heme-binding proteins in the extracellular environment. Work by Sgheiza et al found that while NTHi are able to extract and use heme that is non-covalently bound to proteins, NTHI are unable to efficiently acquire heme that has been covalently bound to protein [59].…”
Section: Iron Acquisitionmentioning
confidence: 99%